Una “nuova stagione” per l’atto politico? Alcune riflessioni tra teoria e prassi costituzionale (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Il “ritorno” dell’atto politico: la stipulazione delle intese con le confessioni religiose - 2. Le origini dell’atto politico tra acte de gouvernement, act of State, political question e acto de gobierno - 3. Gli sviluppi dell’istituto nell’Italia liberale - 4. L’atto politico alla prova della Costituzione - 5. Il ruolo del giudice delle leggi: alcuni casi paradigmatici - 6. Un consuntivo della giurisprudenza costituzionale in tema di atto politico: l’atto di governo come tecnica di giudizio.Is there a “new era” for the act of State in Italy? Some remarks between constitutional theory and practiceABSTRACT: The act of State in the Italian legal system seems now to be heading for a kind of “second drawing”. Starting from the recent judgment n. 52/2016, adopted by the Italian constitutional Court with reference to the agreement between Government and the so-called UAAR, the essay scrutinises the evolution of the act of State in Italy compared to the principles of the constitutional “rule of law”. The analysis deals with both theory and practice, focusing in particular on the approach adopted by the Italian constitutional jurisprudence in order to address political questions.